APLIKASI DOMESTIK SEBAGAI INSTRUMEN KEDAULATAN DIGITAL DAN KEAMANAN NASIONAL: STUDI STRATEGIS ATAS PENDEKATAN TIONGKOK - Ainul Khaliq Asbullah, Andi Anggun; Fadhil Nugraha, Imam (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
The development of information and communication technology has encouraged countries to build new defense strategies to deal with non-traditional threats, including threats to digital sovereignty. China is one country that actively develops and utilizes domestic digital apps as a strategic instrument to protect national security and limit foreign influence in cyberspace. This research aims to analyze how China's strategy of using domestic applications functions as a digital defense fortress and an instrument of sovereignty in the face of global cyber geopolitical dynamics. This research uses a qualitative approach with a descriptive narrative method and literature review. The results show that banning foreign platforms, developing domestic applications, and digital payment systems are part of China's overall strategy in controlling domestic data and information flows. The conclusion of this research confirms that China is not only building technological independence, but also creating a closed and controlled cyberspace as an effort to maintain digital sovereignty and prevent external intervention in national stability China's domestic apps.